2023
DOI: 10.1002/advs.202303907
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte‐Leveraged Oncolytic Virotherapy (ELeOVt): Oncolytic Virus Assembly on Erythrocyte Surface to Combat Pulmonary Metastasis and Alleviate Side Effects

Mingyang Liu,
Ruizhe Zhang,
Hanwei Huang
et al.

Abstract: Despite being a new promising tool for cancer therapy, intravenous delivery of oncolytic viruses (OVs) is greatly limited by poor tumor targeting, rapid clearance in the blood, severe organ toxicity, and cytokine release syndrome. Herein, a simple and efficient strategy of erythrocyte‐leveraged oncolytic virotherapy (ELeOVt) is reported, which for the first time assembled OVs on the surface of erythrocytes with up to near 100% efficiency and allowed targeted delivery of OVs to the lung after intravenous inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…ELeOVt extended the circulation time of OVs after intravenous injection and boosted the transduction efficiency of OVs into tumor cells, demonstrating notable therapeutic efficacy in a murine cancer model with lung metastasis. 166 Other research has reported a chimeric entity of engineered OAs and tumor-specific T cells (including T cell receptor T and CAR-T cells). First, OAs were encapsulated within cell membranes containing tumor-specific antigens (including tumor cells and engineered 293T cells) through lipid squeezing to obtain M@eOA.…”
Section: Np-cell Integrated Delivery Systemsmentioning
confidence: 99%
“…ELeOVt extended the circulation time of OVs after intravenous injection and boosted the transduction efficiency of OVs into tumor cells, demonstrating notable therapeutic efficacy in a murine cancer model with lung metastasis. 166 Other research has reported a chimeric entity of engineered OAs and tumor-specific T cells (including T cell receptor T and CAR-T cells). First, OAs were encapsulated within cell membranes containing tumor-specific antigens (including tumor cells and engineered 293T cells) through lipid squeezing to obtain M@eOA.…”
Section: Np-cell Integrated Delivery Systemsmentioning
confidence: 99%
“…Moreover, safety concerns are another significant issue. The immune activation triggered by OVs can sometimes lead to an excessive inflammatory response, known as a cytokine storm, which can be harmful or even fatal [ 74 , 75 ]. Regulatory and manufacturing challenges also pose significant barriers.…”
Section: Current Status Of Oncolytic Virotherapy In Clinical Settingsmentioning
confidence: 99%